Polusi air untuk materi pembelajaran sains dalam perspektif personal dan sosial - Indyah Sulistyo Arty (LPMPP Universitas Negeri Yogyakarta, 2006)
Several phenomenon of water pollution was happened in Indonesiaan because of pullotants such as detergent, mercury, oil, acid rain, and microbes. The effects of water pollutant showed dangerous to human life.The Subject matter of science about water pollution can be introduced in group of science containet about water pollution in personal and social perspective, which is divided into subject matter group of grade 5 of primary school - grade 2 of junior high school, and subject matter group of grade 3 junior high school - grade 3 of senior high school. As science subject matter, it will be much better for student whend teacher choose subject mater about pollution that has strong relationship with personal and social environment of students.